2022
DOI: 10.3390/ijms232012375
|View full text |Cite
|
Sign up to set email alerts
|

Base and Prime Editing in the Retina—From Preclinical Research toward Human Clinical Trials

Abstract: Inherited retinal diseases (IRDs) are a clinically and genetically heterogeneous group of diseases that are one of the leading causes of vision loss in young and aged individuals. IRDs are mainly caused by a loss of the post-mitotic photoreceptor neurons of the retina, or by the degeneration of the retinal pigment epithelium. Unfortunately, once these cells are damaged, it is irreversible and leads to permanent vision impairment. Thought to be previously incurable, gene therapy has been rapidly evolving to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…This powerful mechanism can be harnessed to knock-out-specific genes or facilitate the insertion of a donor sequence at the DSB site utilising endogenous DNA repair pathways [ 148 , 149 ]. Recent advancements in this technology have given rise to novel editing systems like base and prime editors [ 150 , 151 ]. The field of gene editing is rapidly evolving, expanding the repertoire of available tools and enabling a wider range of edits with increasing precision.…”
Section: Gene-editing Approaches In the Retinamentioning
confidence: 99%
“…This powerful mechanism can be harnessed to knock-out-specific genes or facilitate the insertion of a donor sequence at the DSB site utilising endogenous DNA repair pathways [ 148 , 149 ]. Recent advancements in this technology have given rise to novel editing systems like base and prime editors [ 150 , 151 ]. The field of gene editing is rapidly evolving, expanding the repertoire of available tools and enabling a wider range of edits with increasing precision.…”
Section: Gene-editing Approaches In the Retinamentioning
confidence: 99%
“…Thus, reconstitution occurs at the protein level. 60 , 61 Two recent studies showed interesting results in rd12 mice, an LCA model involving the RPE65 gene with nonsense mutation c.130C>T, p.(R44X). 28 , 62 Both teams performed dual-AAV delivery of split-ABEs to correct point mutation and reached 3% and 6% A>G editing at the DNA level in RPE cells, leading to retinal function improvements.…”
Section: Strategies To Overcome the Aav Size Restrictionmentioning
confidence: 99%
“…Due to the lack of pathogenicity, low immunogenicity, and durable expression of the therapeutic components even in non-dividing cells such as cardiomyocytes, leading AAV-mediated gene replacement therapy is a promising method in treating cardiac disorders [ 22 25 ]. Currently, several AAV serotypes have been identified and applied in both scientific research and clinical treatment [ 26 30 ]. Among them, AAV serotype 9 (AAV9) is considered to be the most effective mammalian cardiomyocyte transducer from systemic injections [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%